Directory of special libraries/information units in Trinidad and Tobago (Ministry of Education Port of SpainTT, 1986)
Contains entries alphabetically arranged by the name of the institution followed by the name and address of the library. Each entry contains relevant information viz. opening hours, contact person, main subjects, telex and telephone numbers. Provides a name index which alphabetically lists the names of the libraries and their reference numbers, and a subject index which is arranged alphabetically.
IDS